Phase II drugs under clinical investigation for the treatment of chronic constipation. (November 2014) - Mozaffari, Shilan; Didari, Tina; Nikfar, Shekoufeh; Abdollahi, Mohammad
<x xml:space="preserve">Abstract</x> Introduction: Chronic constipation (CC) is a common gastrointestinal (GI) motility disorder that significantly impairs the quality of life in affected subjects. As almost half of the patients suffering from CC are not satisfied with currently available medicines, there is a need to develop new molecules with better effectiveness and tolerability. Areas covered: The authors include all experimental and clinical trials (up to Phase II) about new investigational drugs for the treatment of CC. The article identifies nine new agents: mitemcinal, TD-8954, YKP10811, itopride, RM-131, KWA-0711, elobixibat, velusetrag, and naronapride. All nine agents have shown prokinetic effects in different stages of the development. The mechanisms of new developing drugs include: the activation of 5-hydroxytryptamine type-4 (5-HT4), ghrelin and motilin receptors, antagonizing dopamine type-2 (D2) receptors, inhibition of ileal bile acid reabsorption and acetylcholine esterase, as well as water absorption from the GI tract. Expert opinion: At this current point in time, new generations of 5-HT4 receptor agonists (velusetrag, noranopride and YKP10811) are hoped to progress, further in the future, due to better efficiency and safety. However, it is not possible to make a concise conclusion at this current time due to a lack of evidence. Further clinical trials with a longer duration and a larger sample size are warranted.